ESTIMATION OF LATERITE BAUXITE VOLUME USING ORDINARY KRIGING METHOD IN PIASAK VILLAGE, SANGGAU DISTRICT, WEST KALIMANTAN: ESTIMASI VOLUME BAUKSIT LATERIT MENGGUNAKAN METODE ORDINARY KRIGING DI DESA PIASAK, KABUPATEN SANGGAU, KALIMANTAN BARAT - Murti, Tiffany Budi; Eldoni, Andika; Muhardi; Perdhana, Radhitya (Buletin Sumber Daya Geologi, 2025)
West Kalimantan Province is one of the largest bauxite-producing areas in Indonesia, with total reserves of 0.85 billion tons from 1.26 billion tons of national reserves. One of the areas with potential bauxite in Sanggau Regency, West Kalimantan, is Piasak Village. Estimating bauxite resources is an essential step in identifying reserves in a mining area. This study aims to estimate the volume of laterite bauxite in Piasak Village, Sanggau Regency. This study applies the ordinary kriging estimation method based on test pit samples at 47 locations. Data processing was conducted using QGIS and Saga GIS software. The statistics calculation of bauxite deposit thickness data obtained a coefficient of variation of 0.2, indicating that the samples were homogeneous. The spherical semivariogram model was used for the kriging estimation process of bauxite deposit thickness because it had the smallest root mean square error. The parameter values for nugget, sill, and range were 0.08 m2, 1.15 m2, and 100.9 m, respectively. The estimation results show that the volume of laterite bauxite at the study site is 180,051 m3, while the volume of overburden is 56,796 m3.